Ring of truth a translator's testimony - Phillips, John Bertram, 1906-1982 (London, UK Hodder and Stoughton, 1967)
Includes bibliographical references.
Keywords: Phillips, John Bertram, -- 1906-82; Biblical scholars -- biography; Bible translation